Bad summer people - Rosenblum, Emma (2023)
"Emma Rosenblum's Bad Summer People is a whip-smart, propulsive debut about infidelity, backstabbing, and murderous intrigue, set against an exclusive summer haven on Fire Island. None of them would claim to be a particularly good person. But who among them is actually capable of murder? Jen Weinstein and Lauren Parker rule the town of Salcombe, Fire Island every summer. They hold sway on the beach and the tennis court, and are adept at manipulating people to get what they want. Their husbands, Sam and Jason, have summered together on the island since childhood, despite lifelong grudges and numerous secrets. Their one single friend, Rachel Woolf, is looking to meet her match, whether he's the tennis pro-or someone else's husband. But even with plenty to gossip about, this season starts out as quietly as any other. Until a body is discovered, face down, off the side of the boardwalk. Stylish, subversive, and darkly comedic, this is a story of what's lurking under the surface of picture-perfect lives in a place where everyone has something to hide"--
Keywords: Summer -- Fiction; Murder -- Investigation -- Fiction; Gossip -- Fiction; Vacation homes -- Fiction; Adultery -- Fiction; Rich people -- Fiction; Single women -- Fiction; Fire Island (N.Y. : Island) -- Fiction; Thrillers (Fiction); Novels